Pemberdayaan Pengusaha Batik sebagai Penggerak Perekonomian di Desa Pabean Udik Kabupaten Indramayu - Ratna Hindria Dyah Pita Sari; Erna Hernawati; Masripah Masripah; Praptiningsih Praptiningsih (Universitas Persada Indonesia YAI, 2023)
The batik entrepreneurs in Pabean Udik Village are not optimal in developing their businessbecause of problems related to production and marketing. Entrepreneurs do not understand theexact capital cost calculation system and have not made financial reports that are in accordancewith accounting rules. This causes the determined selling price to often experience errors indetermining the cost of goods sold (COGS) which has an impact on the amount of gross profit. Inaddition, batik entrepreneurs do not pay attention to product marketing techniques, and do not evenhave a special concept in packaging their products. Based on the initial visit of the communitydedication team, the fact that the craftsmen only use plastic bags in packaging their products.However, this seems to be due to the fact that batik entrepreneurs have just risen since their businesshas decreased due to the Covid-19 pandemic. So they focus their business capital on product rawmaterials, not for packaging. Entrepreneurs also do not conduct online promotions or sales to invitebuyers. They only market by word of mouth and maintain their customers. With these problems, apersuasive approach and training are needed that are easily understood by batik entrepreneurs withall their limitations so that the services they carry out provide progress for the business managementsystem for batik entrepreneurs in Pabean Udik Village. The method of implementing this serviceconsists of surveys, interviews, and observations. Economic empowerment is carried out by trainingbatik entrepreneurs in Pabean Udik Village regarding basic accounting, introduction of quality raw materials, attractive product design and selling, as well as business digitization with training on theuse of marketplaces. With this training, it is hoped that batik entrepreneurs can apply the knowledgegained and be useful for the implementation of their business operations